2018
DOI: 10.1007/s10919-018-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal Synchrony and Complementarity in Unacquainted Same-Sex Dyads: A Comparison in a Competitive Context

Abstract: Research on interpersonal synchronization deals with the coordination of behavior, cognition and affect within interacting individuals. The phenomenon of synchronization has been explored in many settings and numerous definitions have emerged. The purpose of this study was to compare nonverbal synchrony (based on overall body movement) with the concept of complementarity (based on interpersonal theory) in a competitive context. We examined 40 previously unacquainted same-sex dyads (21 female, 19 male; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Some of the existing literature on nonverbal synchrony suggests that an increase of synchrony is associated with better relationship quality (Ramseyer & Tschacher, ), positive affect (Tschacher et al , ), and appears to be linked with dyads characterized by high affiliative complementarity (Lozza et al , ). Other studies failed to find clear associations with affect (Paxton & Dale, ) or indicated that an optimal level of synchrony would lie somewhere in between the extremes of low versus high synchrony (Paulick, Deisenhofer et al , ), and that synchrony was dependent on patient's diagnosis (Paulick, Rubel et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the existing literature on nonverbal synchrony suggests that an increase of synchrony is associated with better relationship quality (Ramseyer & Tschacher, ), positive affect (Tschacher et al , ), and appears to be linked with dyads characterized by high affiliative complementarity (Lozza et al , ). Other studies failed to find clear associations with affect (Paxton & Dale, ) or indicated that an optimal level of synchrony would lie somewhere in between the extremes of low versus high synchrony (Paulick, Deisenhofer et al , ), and that synchrony was dependent on patient's diagnosis (Paulick, Rubel et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Where coaches conducted 60-min sessions, they delivered 10 video-taped files while others provided fewer video-recorded sessions where their engagement was to end sooner according to the coaching contract. For the purposes of automated video-analysis in coaching as a non-clinical helping intervention, it was assumed that the clients, who were not subject to inclusion or exclusion criteria based on diagnosis (e.g., psychosis, substance dependency), would have a normal capacity to synchronize nonverbally as observed in student dyads (Lozza et al, 2018 ; Fujiwara et al, 2019 ; Dunbar et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the time series may be truncated to identical lengths as realized in most experimental applications (e.g. Tschacher, Rees & Ramseyer, 2014;Lozza et al, 2018). Naturalistic data with different durations may be cut into equal segments and results later aggregated (e.g.…”
Section: Computation Of Physiological Synchronymentioning
confidence: 99%